2016
DOI: 10.1183/16000617.0044-2016
|View full text |Cite
|
Sign up to set email alerts
|

Exertional dyspnoea in cardiorespiratory disorders: the clinical use of cardiopulmonary exercise testing

Abstract: @ERSpublicationsA series of articles on exertional dyspnoea in cardiorespiratory disorders begins in the European Respiratory Review http://ow.ly/fLT0300uHgwIs dyspnoea worth documenting and accurately assessing? The answer is undoubtedly yes, for at least the following reasons. 1) Activity-related dyspnoea is usually the earliest and most troublesome complaint for which patients with cardiopulmonary diseases seek medical attention. 2) This symptom progresses relentlessly as the underlying disease advances, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The mechanisms orchestrating the ergogenic effect of heliox and oxygen breathing on exercise capacity were not limited to the alleviation of ventilatory constraints during exercise. The results from this case and other studies suggest that extrapulmonary improvements could potentially alleviate exercise induced-dyspnoea in patients with COPD [17, 18]. Furthermore, during heliox and oxygen breathing the patient exhibited improved respiratory and locomotor muscle metabolic condition as indicated by the smaller decrease in local muscle oxygenation that was accompanied by less lactic acidosis as compared with room air (figure 3).…”
Section: Discussionsupporting
confidence: 54%
“…The mechanisms orchestrating the ergogenic effect of heliox and oxygen breathing on exercise capacity were not limited to the alleviation of ventilatory constraints during exercise. The results from this case and other studies suggest that extrapulmonary improvements could potentially alleviate exercise induced-dyspnoea in patients with COPD [17, 18]. Furthermore, during heliox and oxygen breathing the patient exhibited improved respiratory and locomotor muscle metabolic condition as indicated by the smaller decrease in local muscle oxygenation that was accompanied by less lactic acidosis as compared with room air (figure 3).…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, when dyspnoea is not explained by pulmonary or cardiac investigations, it is reasonable to submit symptomatic patients to cardiopulmonary exercise testing (CPET). The importance of CPET has recently been summarized for cardiopulmonary as well as respiratory disorders . Here, we mainly emphasize that easily available PFT may be of added value in the functional characterization of patients with chronic HF with or without respiratory co‐morbidities.…”
Section: Pulmonary Function Testing In Heart Failurementioning
confidence: 99%
“…For instance, a recent study demonstrated that in patients with mild COPD, parameters of CPET have a strong association with D LCO . Nevertheless, CPET parameters may provide important additional information in individual patients, and detailed recommendations for this test have been summarized elsewhere …”
Section: Pulmonary Function Testing In Heart Failurementioning
confidence: 99%
“…In this study, we found that reduced exercise capacity in patients with CHF was associated with an increased level of dyspnea, independent of the number of comorbidities and the ejection fraction of the left ventricle. An increased level of dyspnea during exercise is the hallmark of exercise intolerance in patients with CHF [25,26]. Dyspnea is multidimensional and derives from interactions between several domains, including physiological, psychological, social, and environmental factors [27].…”
Section: Discussionmentioning
confidence: 99%